Odpowiedź :
Odpowiedź:
1/ ( √6-√5) = (√6+√5) / ( √6-√5)(√6+√5) = ( √6+√5) / (6-5)= √6+√5
4/ (2-√2)= 4*(2+√2) / (2-√2)(2+√2)= 4*(2+√2) / ( 4-2)= 2*( 2+√2)=4+2√2
4/( √3+√5)= 4*(√3-√5) / ( √3+√5)(√3-√5)= 4*(√3-√5) /( 3-5)= -2(√3-√5)=
2√5-2√3
Szczegółowe wyjaśnienie:
Szczegółowe wyjaśnienie:
[tex] \frac{ \sqrt{6} + \sqrt{5} }{( \sqrt{6} - \sqrt{5} )( \sqrt{6} + \sqrt{5)} } = \frac{ \sqrt{6} + \sqrt{5} }{6 - 5} = \sqrt{6} + \sqrt{5} [/tex]
[tex] \frac{4 \times (2 + \sqrt{2)} }{(2 - \sqrt{2} ) \times (2 + \sqrt{2} )} = \frac{4 \times (2 + \sqrt{2}) }{4 - 2} = 2 \times (2 + \sqrt{2)} [/tex]
[tex] \frac{4 \times ( \sqrt{3 } - \sqrt{5)} }{( \sqrt{3} + \sqrt{5} ) \times ( \sqrt{3} - \sqrt{5} )} = \frac{4 \times ( \sqrt{3} - \sqrt{5)} }{ 3-5} = - 2 \times ( \sqrt{3} - \sqrt{5} ) = 2 \sqrt{5} - 2 \sqrt{3} [/tex]